2010
DOI: 10.1074/jbc.m110.145938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Site-specific Glycosylation of Renal and Hepatic γ-Glutamyl Transpeptidase from Normal Human Tissue

Abstract: The cell surface glycoprotein ␥-glutamyl transpeptidase (GGT) was isolated from healthy human kidney and liver to characterize its glycosylation in normal human tissue in vivo. GGT is expressed by a single cell type in the kidney. The spectrum of N-glycans released from kidney GGT constituted a subset of the N-glycans identified from renal membrane glycoproteins. Recent advances in mass spectrometry enabled us to identify the microheterogeneity and relative abundance of glycans on specific glycopeptides and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
55
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 53 publications
8
55
1
Order By: Relevance
“…The only evidence that hGGT2 transcripts are actively translated in vivo is a report in which a single tryptic peptide unique to the amino-acid sequence of hGGT2 was identified during a high-throughput mass spectrometric characterization of human liver glycopeptides (7). However, we did not detect hGGT2-specific peptides within the pool of tryptic fragments from protein immunopurified from normal human kidney and liver with our GGT129 antibody (51,52). This antibody was developed against a peptide that is identical in hGGT1 and all three variants of hGGT2 [ Fig.…”
Section: Discussionmentioning
confidence: 46%
“…The only evidence that hGGT2 transcripts are actively translated in vivo is a report in which a single tryptic peptide unique to the amino-acid sequence of hGGT2 was identified during a high-throughput mass spectrometric characterization of human liver glycopeptides (7). However, we did not detect hGGT2-specific peptides within the pool of tryptic fragments from protein immunopurified from normal human kidney and liver with our GGT129 antibody (51,52). This antibody was developed against a peptide that is identical in hGGT1 and all three variants of hGGT2 [ Fig.…”
Section: Discussionmentioning
confidence: 46%
“…GGTP is found in organisms from bacteria to mammals and plants. Literature data concerning GGTP biochemical properties showed evidence of high thermostability, independence of pH variations, and stability in high-salt conditions (16)(17)(18)(19)(20)(21). AMPs comprise a large family of biologically important zinc enzymes playing different roles in the regulation of blood pressure, antigen presentation, memory, cell cycle, pregnancy, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…3, E and F). N-glycosylation at Asn-297 occurred in hGGT1 isolated from human tissues but was absent in the crystal structure of the yeast-expressed hGGT1 (35).…”
Section: Table 1 Data Collection and Refinement Statisticsmentioning
confidence: 99%
“…Previous studies on the N-glycosylation pattern of hGGT1 isolated from human tissues identified seven N-glycosylation sites (35,36). Because we trimmed the glycans to the proximal glycan with Endo H f before crystallization, the N-glycosylation sites were marked by one GlcNAc residue.…”
Section: Table 1 Data Collection and Refinement Statisticsmentioning
confidence: 99%
See 1 more Smart Citation